RESEARCHES ON ENGLISH AND UZBEK TERMINOLOGY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This thesis provides an in-depth investigation into the creation, development, and usage of terminology in It also explores field-specific terminology in areas like medicine, information technology, and law, analyzing the mechanisms of borrowing, calquing, and adaptation used to incorporate foreign terms.The thesis underscores the challenges of creating standardized terms in Uzbek while addressing cultural and linguistic differences.This research contributes to understanding the role of terminology in facilitating precise communication across languages and disciplines, offering valuable insights for linguists, translators, and language planners